Oil price shocks: A comparative study on the impacts of oil price movements in Malaysia and the UK economies - Hidthiir, Mohamad Helmi; Azman Aziz, Mukhriz Izraf; Fadzim, Wan Roshidah (2007)
The study investigates the relationship between changes in crude oil prices and Malaysia and the UK macro-economy. A multivariate VAR analysis is carried out among five key macroeconomic variables: real gross domestic product, short term interest rate, real effective exchange rates, long term interest rate and money supply. From the VAR model, the impulse response functions reveal that oil price movements cause significant reduction in aggregate output and increase real exchange rate. The variance decomposition shows that crude oil prices significantly contribute to the variability of real exchange rate long term interest rate in the Malaysia economy while oil price shocks are found to have significant effects on money supply and short term interest rate in the UK economy. Despite these macro-econometric results, caution must be exercised in formulating energy policies since future effects of upcoming oil shocks will not be the same as what happened in the past. Explorations and development of practicable alternatives to imported fuel energy will cushion the economy from the repercussions of oil shocks.